Mogroside V-producing Endophytic Fungi Isolated from Siraitia grosvenorii - Bin, Chen; Fangming, Yu; Zhi, Jiang (Planta Medica, 2020)
Endophytic fungi can produce beneficial active components during symbiosis with host plants. Fifteen purified endophytic fungal strains were isolated and screened from root, stem, leaf, and fruit of the Chinese medicine food homologous plant Siraitia grosvenorii. These strains were fermented, and then the fermented solution was extracted using acetonitrile. The extracts were analyzed by high performance liquid chromatography (HPLC) and mass spectrum (MS), using standard mogroside V as control. The results showed that strain LHG-F5 and strain LHG-L4 could produce mogroside V with output of 3.814 µg/mL and 2.675 µg/mL, respectively. By morphological observation together with similarity of internal transcribed spacer (ITS) sequence by Clustan X method, LHG-F5 and LHG-L4 were classified as Diaporthe angelica and Fusarium solani, respectively.
Keywords: Siraitia grosvenorii; Cucurbitaceae; endophytic fungi; mogroside V; HPLC; LC-MS